Compressing Natural Gas - Carbon Capture - EOR (CAGAR) Innovation: Cost Effective Sustainable Flare Gas Utilization to Boost Oil Production - Sasa Aulia (Inovbook Publications, 2022)
Drilling natural gas (CNG) is a promising environmentally friendly gasoline substitute. It is produced at a reasonable price. Flaring, on the other hand, emits 300 million tons of CO2 into the environment wasting vital energy resources. As a result, rather than releasing CO2 into the atmosphere, it is used to boost oil production as a CO2 EOR to fulfill global oil demand that continues to rise. To achieve a sustainable oil and gas production by reducing greenhouse gasses (GHG) through flaring reduction innovations comprising gas purification and carbon capture that utilizes the associated gas as a viable compressed natural gas (CNG) and enhanced the oil recovery. Natural gas linked with crude oil (CH4 dominated) is processed in two units. The first one is a gas purification unit where natural gas is purified in compressor, Acid Gas Removal Unit (AGRU), dehydration unit, and hydrocarbon recovery producing viable CNG. In the flaring unit gas is burned converting the CH4 to CO2. Flared gas is captured in a Carbon Capture Storage (CCS). Furthermore, CO2 is centralized in the EOR-System to be injected into the reservoir as CO2-EOR by interacting with oil causing oil to swell and reduce its viscosity leading to oil flow easier through the pores. This research elucidates that CAGAR could produce 2,970 mmbtu/d of CNG. Beside producing profitable products, CAGAR also boosted oil production by adding an extra 21,369.6 bbl/d oil recovery. According to the results, the production of the CAGAR method of flare gas utilization is the most economical technology with an annual sales from oil recovery and CNG of 455,768,373 USD so that CAGAR get a profit before tax of 248,288,632.81 USD and a profit after tax of 207,479,740.57 USD with a parameter calculation is a positive NPV, IRR of 30.26% including the cash flow and present value start to be positive in the 3rd year when the system starts operating. CAGAR has a payback period of 2.7 years. Technical and economic analysis shows there improved oil recovery and improved environmental protection. So it can be concluded that CAGAR has good prospects and deserves to be implemented.